2015
DOI: 10.1007/s10147-015-0903-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors after imatinib secondary resistance: survival analysis in patients with unresectable and metastatic gastrointestinal stromal tumors

Abstract: Surgical resection of PD in selected cases could improve prognosis in ISR patients undergoing GIST treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Of 24 patients who underwent surgical resection of progressive diseases (PD), 20 did so as second-line treatment after imatinib therapy. Long PFS in first-line imatinib therapy, small diameter of PD and surgical resection of PD were identified as favorable independent prognostic factors (40).…”
Section: Front-line Surgery Prior To Imatinib Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Of 24 patients who underwent surgical resection of progressive diseases (PD), 20 did so as second-line treatment after imatinib therapy. Long PFS in first-line imatinib therapy, small diameter of PD and surgical resection of PD were identified as favorable independent prognostic factors (40).…”
Section: Front-line Surgery Prior To Imatinib Therapymentioning
confidence: 99%
“…In 2017, these two American institutes collected their data, analyzed clinicopathological data of 400 surgeries on 323 patients with TKI-treated metastatic GIST, and reported that surgery for metastatic imatinibtreated GIST in the absence of multifocal progressive disease was associated with outcomes at least comparable with second-line sunitinib, and may be considered in select patients (32). Kanda et al retrospectively analyzed 48 patients with unresectable and metastatic GISTs who were diagnosed with imatinib secondary resistance (ISR) and/ or underwent treatment for ISR (40). Of 24 patients who underwent surgical resection of progressive diseases (PD), 20 did so as second-line treatment after imatinib therapy.…”
Section: Front-line Surgery Prior To Imatinib Therapymentioning
confidence: 99%
“…There were 4 and 2 studies on the long-term outcomes after surgery for metastatic or recurrent GIST with partial resistance and systemic resistance to imatinib, respectively. Postoperative PFS and OS were better in the partial resistance group than in the systemic resistance group [ 93 , 126 128 ]. There was only one study that compared patients with and without surgery for sunitinib-resistant GIST.…”
Section: Surgical Management Partmentioning
confidence: 99%